Ashes - Lasky, Kathryn (New York : Viking, 2010)
In 1932 Berlin, thirteen-year-old Gaby Schramm witnesses the beginning of Hitler's rise to power, as soldiers become ubiquitous, her beloved literature teacher starts wearing a jewelled swastika pin, and the family's dear friend, Albert Einstein, leaves the country while Gaby's parents secretly bury his books and papers in their small yard.
Booklist starred
Publisher's Weekly
Booklist starred, January 2010
Publisher's Weekly, January 2010
6.9
5-8.
Keywords: Families -- Germany -- Juvenile fiction; Nazis -- Juvenile fiction; Family life -- Germany -- Fiction; Historical fiction; Nazis -- Fiction; Family life -- Germany -- Fiction; Historical fiction; Nazis -- Fiction; Germany -- History -- 1918-1933 -- Juvenile fiction; Germany -- History -- 1918-1933 -- Fiction; Germany -- History -- 1918-1933 -- Fiction; Historical fiction